COVID-19 Pandemic Impact on Sickness Absences Among Healthcare Workers: A Cohort Study in a Spanish Hospital (2018-2023) - López-Millán , Brais; Benavides, Fernando G; Ramada, Jose Maria; Serra, Consol; Serra, Laura; Utzet, Mireia (La Medicina del Lavoro, 2025)
Background: Like other European systems, the Spanish national health system (NHS) is reaching a critical point. This article analyses sickness absence (SA) trends, as a direct indicator of this crisis, among healthcare workers (HCWs) in Spain, comparing the pre-pandemic, pandemic, and post-pandemic periods. Methods: This study was based on a retrospective cohort of HCWs (n=7.918) hired at Hospital del Mar in Barcelona for at least three months during 2018-2023. The primary outcome was incident SA episodes. Incidence rates (IR) per 1,000 persons-day and 95% confidence intervals (95% CI) were calculated by sex, period, and occupational variables. Longitudinal entropy regression models were estimated to identify the factors influencing the frequency of transitions between the different HCWs’ employment states (active or on SA). Results: Increasing trends in IR (95%CI) were observed, rising from 1.77 (1.71; 1.83) episodes of SA per 1,000 workers-day during the pre-pandemic period to 5.04 (4.93; 5.15) during the post-pandemic among women, and from 1.23 (1.14; 1.31) to 3.79 (3.64; 3.95), respectively, among men. Nurses, nurse aides, orderlies/technicians, workers under 30, and those in intensive care units and emergency rooms showed the highest IR during and after the pandemic, with longitudinal entropy analysis revealing increased state changes, primarily affecting these groups. Conclusions: This study demonstrates a significant rise in SA incidence among HCWs during and after the pandemic and identifies vulnerable groups with higher incidence. Several hypotheses, such as poor working conditions, burnout, and patient complexity, have been suggested to explain these results. Urgent interventions are needed to safeguard HCWs’ health, thus maintaining the sustainability and safety of the NHS.